Verwaltungsnetzwerke als Organisationsform föderaler Kooperation Eine Untersuchung anhand der gemeinsamen Umsetzung des Onlinezugangsgesetzes durch Bund, Länder und Kommunen - Voss, Vivien Carlotta (Verwaltungswissenschaften in juristischer Perspektive, 2023)
A digital administration requires new forms of cooperation. The work focuses on administrative networks as a form of organisation and shows legal possibilities of implementation through administrative networks on the basis of the "Onlinezugangsgesetz" (Online Access Act). Networks are analysed from the perspective of administrative law, taking into account the constitutional framework. The network characteristics identified are applied to the cooperation for im-plenting the Online Access Act and legal options for action are examined. Thus, the work is aimed at administrative law scholars with a focus on digital administration as well as representatives from federal, state and local administration.